The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1063/1.5025382
|View full text |Cite
|
Sign up to set email alerts
|

Improved dielectric properties of Ag@TiO2/PVDF nanocomposites induced by interfacial polarization and modifiers with different carbon chain lengths

Abstract: In this study, poly(vinylidene fluoride) (PVDF)-based nanocomposites filled with surface-functionalized Ag@TiO2 core-shell nanoparticles were fabricated in order to achieve high dielectric permittivities. Using two phosphonic acid surfactants with differing carbon chain lengths, octyl and octadecyl phosphonic acid, the filler surfaces were modified to improve the dispersion of the core-shell filler in PVDF. The experimental results showed that the dielectric constant of the composite with fillers modified usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 20 publications
0
15
1
Order By: Relevance
“…Unfortunately, the ε′ values of the TiO 2 /polymer composites are still significantly low owing to the low ε’ of the TiO 2 nanoparticles. Polymer composites filled with modified TiO 2 nanoparticles such as Ag-TiO 2 hybrid particles and Ag@TiO 2 core–shell structures were developed to enhance ε′ [ 34 , 35 , 36 , 37 ]. Although these composites can exhibit high ε′ values of ~60–150, large tanδ values are generally obtained (~0.1–1) at high filler concentrations (70 vol%) [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, the ε′ values of the TiO 2 /polymer composites are still significantly low owing to the low ε’ of the TiO 2 nanoparticles. Polymer composites filled with modified TiO 2 nanoparticles such as Ag-TiO 2 hybrid particles and Ag@TiO 2 core–shell structures were developed to enhance ε′ [ 34 , 35 , 36 , 37 ]. Although these composites can exhibit high ε′ values of ~60–150, large tanδ values are generally obtained (~0.1–1) at high filler concentrations (70 vol%) [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polymer composites filled with modified TiO 2 nanoparticles such as Ag-TiO 2 hybrid particles and Ag@TiO 2 core–shell structures were developed to enhance ε′ [ 34 , 35 , 36 , 37 ]. Although these composites can exhibit high ε′ values of ~60–150, large tanδ values are generally obtained (~0.1–1) at high filler concentrations (70 vol%) [ 34 , 35 ]. Among various metal nanoparticles, gold nanoparticles are widely used as fillers to improve the insulation properties of polymer materials because they are nontoxic and less likely to be oxidized [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…At f Ag −INTO = 0.5, the σ ac value at 1 kHz was only 2.13 × 10 −9 S/cm at 1 kHz. This is much lower than that of other three-phase composite systems, which is usually >10 −7 S/cm [ 25 , 34 ]. Thus, it is clearly confirmed that no conducting pathway was formed.…”
Section: Resultsmentioning
confidence: 77%
“…The enhanced conductivity and tanδ due to incorporation with conductive particles can be inhibited by the discrete growth of metal particles on the surface of ceramic particles. Many previous works showed that a significantly enhanced ε′ and low tanδ of these three-phase composites are achieved [ 3 , 26 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…To meet the developing trends of miniaturization and integration of electronic systems, various different fillers have been embedded in polymers [5]. Among the various structures for fillers, a filler with a core-shell structure has attracted considerable interest, owing to its combination of favorable core and shell properties [6,7,8].…”
Section: Introductionmentioning
confidence: 99%